2007
DOI: 10.1021/nl070915c
|View full text |Cite
|
Sign up to set email alerts
|

Directly Synthesized Strong, Highly Conducting, Transparent Single-Walled Carbon Nanotube Films

Abstract: We report the direct synthesis of strong, highly conducting, and transparent single-walled carbon nanotube (SWNT) films. Systematically, tests reveal that the directly synthesized films have superior electrical and mechanical properties compared with the films made from a solution-based filtration process: the electrical conductivity is over 2000 S/cm and the strength can reach 360 MPa. These values are both enhanced by more than 1 order. We attribute these intriguing properties to the good and long interbundl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
320
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 345 publications
(333 citation statements)
references
References 26 publications
10
320
0
1
Order By: Relevance
“…We are encouraged by this as at this stage the CNT synthesis process has not yet been optimized for the combination of optical transparency and electrical conductivity, nor have any post-processing treatments been Conductance against transparency for different nanotube films. Our own results (solid circles for free-standing, squares for polymer-backed) are compared against the results of Budhadipta et al [7] (upright triangles), Geng et al [6] (inverted triangles), Zhou et al [5] (diamonds), Ma et al [8] (left-pointing triangles), Kaempgen et al [15] (stars), Green and Hersam [16] (right-pointing triangles) and Yu et al [17] (empty circles).…”
Section: Transparency and Electrical Conductivitymentioning
confidence: 93%
See 1 more Smart Citation
“…We are encouraged by this as at this stage the CNT synthesis process has not yet been optimized for the combination of optical transparency and electrical conductivity, nor have any post-processing treatments been Conductance against transparency for different nanotube films. Our own results (solid circles for free-standing, squares for polymer-backed) are compared against the results of Budhadipta et al [7] (upright triangles), Geng et al [6] (inverted triangles), Zhou et al [5] (diamonds), Ma et al [8] (left-pointing triangles), Kaempgen et al [15] (stars), Green and Hersam [16] (right-pointing triangles) and Yu et al [17] (empty circles).…”
Section: Transparency and Electrical Conductivitymentioning
confidence: 93%
“…Popular methods for this deposition include inkjet printing [5] and air spraying [6]; recently a draw-down rod coating method has been reported [7] with impressive conductivity. Direct synthesis procedures reported to date have required the nanotube film to be peeled off a quartz substrate [8], a factor that would limit the transparency of the films produced (as the films will need a certain amount of thickness to provide mechanical integrity) and has questionable scalability. It would be advantageous to be able to produce functional transparent nanotube films in a single step, allowing greater control over tube alignment in the film, faster production and easy scalability.…”
Section: Introductionmentioning
confidence: 99%
“…[14][15] Such films are different from conventional SWCNT films prepared by other post-deposition methods that produce short and randomly-oriented structures. A continuous reticulate architecture endows directly synthesized films superior electrical conductivity (about 2000 S/cm) and better mechanical properties than that of post-deposited SWCNT films.…”
Section: Cnts-based Flexible Edlcsmentioning
confidence: 97%
“…Besides the aligned CNT structure, random network structures of CNTs have also been investigated to realize stretchable transparent electrodes via solution-based coating [85,86], floating catalyst CVD (FCCVD) [87][88][89], and electrospinning [90]. The stretchability of the random network differs from that of the aligned network of CNTs, and the random network can be biaxially stretched.…”
Section: Random Network Cntsmentioning
confidence: 99%
“…By flowing a catalyst source and reaction gas into a chamber at the same time, free-standing SWCNTs can be directly synthesized onto a substrate, as shown in Figure 4(e) [87]. Xie et al reported an FCCVD-synthesized SWCNT random network as a stretchable transparent electrode.…”
Section: Random Network Cntsmentioning
confidence: 99%